-6y+3 = -7y+8 -6y+7y = 8-3 y = 5
This simplifies to 6+13y If you meant 9+7y-(3+6y) then it becomes 6+y It is not clear from the problem which you meant.
7y-8 = 6y+1 7y-6y = 1+8 y = 9
6y=5y+2y 6y=7y that does't work its unequal -
10
-8x-6y=-18
y-5x
7y+3=y+18 Subtract three 7y=y+15 Subtract y 6y=15 Divide Y=15/6 That's your fraction if you need a decimal just type it in the calculator...
The given expressions can be simplified to: 7y-8x-14
y-3x+6y=12 7y=3x+12 y=3x/7 +12/7
The simplified expression is 3x - 7y.
Steps: y - 7y + 6 = 30 -6y + 6 = 30 -6y + 6 - 6 = 30 - 6 -6y = 24 -6y / -6 = 24 / -6 y = -4 Check work: -4 - 7(-4) + 6 = 30 -4 - (-28) + 6 = 30 -4 + 28 + 6 = 30 24 + 6 = 30 30 = 30